Model-based brain and tumor segmentation - Moon, N.; Bullitt, E.; van Leemput, K.; Gerig, G. (International Conference on Pattern Recognition, 2002)
Combining image segmentation based on statistical classification with a geometric prior has been shown to significantly increase robustness and reproducibility. Using a probabilistic geometric model and image registration serves both initialization of probability density functions and definition of spatial constraints. A strong spatial prior however prevents segmentation of structures that are not part of the model. Our driving application is the segmentation of brain tissue and tumors from three-dimensional magnetic resonance imaging (MRI). Our goal is a high-quality segmentation of both healthy tissue and tumor. We present an extension to an existing expectation maximization (EM) segmentation algorithm that modifies a probabilistic brain atlas with an individual subject's information about tumor location obtained from subtraction of post- and pre-contrast MRI. The new method handles various types of pathology, space-occupying mass tumors and infiltrating changes like edema. Preliminary results on five cases presenting tumor types with very different characteristics demonstrate the potential of the new technique for clinical routine use for planning and monitoring in neurosurgery, radiation oncology, and radiology.